ATTITUDE TOWARDS HALAL PRODUCTS: ANTESENDEN AND ITS CONSEQUENCES (Empirical Studies on Consumers of Halal Beauty Products in Pati) - Uun Itsna Qoniatin (UNISSULA, 2018)
This research is motivated by the increase of cosmetic business (skin care) halal very rapidly. This can be seen from the many brands of halal skin care in companies that stand in Indonesia, especially in the city of Pati, among others: Tamara Skincare, Julie Skincare, Alzena Skincare, Derma Skincare, Vz Skincare, Sifra Skincare, Corpoderma and many more. The phenomenon of increasing consumer of halal beauty products at skin care clinic proves consumers are more religious in behaving to run as a Muslim, but in fact there are many cases that occur caused by the content of harmful substances in cosmetics that result in many skin diseases. By looking at the existing problems, this research is aimed to analyze how to improve consumer buying intention on kosher beauty cosmetics in Pati Regency through Religiusitas, Dimension of Ideology, Ritualistic, Intellectual, Experience, Consequences and Attitudes toward Halal Products. This research was conducted on consumers of halal beauty products in Pati City involving 200 respondents. The sampling technique used in this research is purposive sampling. Tests in this study using SPSS 16.0. The result showed that the variables of Religiusity, Ideology, Ritualistic, Intellectual, Experience have positive effect toward attitude toward halal product, consequence variable have negative effect toward attitude toward halal product, variability of religiosity have positive effect on buying intention, and attitude toward halal product have positive effect to halal products.Keywords : Religiosity, deological Dimension, Ritualistic Dimension, Intellectual Dimension, ExperienceDimension, Consequence Dimension, Attitudes toward Halal Products, Intention to Buy.